A Mobile Web Application Architecture For Generating Destination Oriented LRT Route - Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan; Kamalrudin, Massila; Abdullah, Muhammad Haziq Lim (2008)
Integrated Light Rail Transit (LRT) System in the capital of Malaysia connects some key districts where historical places, interesting places, business areas and shopping malls are concentrated. The train services are running independently but have points where they have interchanges. This may leads the traveler facing difficulty when they are choosing incorrect destination station especially on different LRT lines which contribute to time consuming and high costing. Thus, Dynamic Route Map (DRM) is proposed where the destination-oriented routes need to be dynamically generated by determining the nearest station according to the specific places. In this paper, we present an architecture in developing mobile application that runs on a Personal Digital Assistant (PDA) to provide the solution for traveler to reach the desired destination.